2007
DOI: 10.1038/nphys679
|View full text |Cite
|
Sign up to set email alerts
|

Bridging length scales in colloidal liquids and interfaces from near-critical divergence to single particles

Abstract: Boiling and condensation are among the best recognized phase transitions of condensed matter. Approaching the critical point, a liquid becomes indistinguishable from its vapour, the interfacial thickness diverges and the system is dominated by long-wavelength density fluctuations 1 . Long wavelength usually means hundreds of particle diameters, but here we consider the limits of this assumption, using a mesoscopic analogue of simple liquids, a colloid-polymer mixture 2,3 . We simultaneously visualize both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 30 publications
2
28
0
Order By: Relevance
“…At elevated T , measurements of γ(q; T ) using GISAXS are challenging due to the significant vapour density. However, -v-like interfaces in suitable colloidal suspensions can be studied well [48] even close to criticality [49], which allows one to analyse γ(q; T ) along the lines presented here.…”
Section: Definition Of γ(Q)-mentioning
confidence: 99%
“…At elevated T , measurements of γ(q; T ) using GISAXS are challenging due to the significant vapour density. However, -v-like interfaces in suitable colloidal suspensions can be studied well [48] even close to criticality [49], which allows one to analyse γ(q; T ) along the lines presented here.…”
Section: Definition Of γ(Q)-mentioning
confidence: 99%
“…[29][30][31] This development means that the structure of experimental systems that display Brownian motion can now be analysed with higher-order structural detection algorithms, with interest in, for example, colloidal gels, 32 glasses, 29 and critical fluctuations. 33 Here we describe a recent addition to the collection of high-order structural detection algorithms, the topological cluster classification (TCC) algorithm. This algorithm has been used to investigate higher-order structure in colloidal 32,34 and molecular 35 gels, colloid-polymer mixtures, 36 colloidal clusters, [37][38][39] simple liquids, 60 liquidvapor interfaces, 40 supercooled liquids, [41][42][43] and crystallising fluids.…”
Section: Introductionmentioning
confidence: 99%
“…The length scale of forces generated by polymer addition can be varied by the degree of polymerization, the concentration, and the polymer structure. 18 In a recent publication, Feng et al 23 reported interesting reentrant flocculation behavior of colloidal particles in an aqueous dispersion containing polymers. Several different polymer and particle combinations were investigated, but the ones displaying the re-entrant behavior had one common property: a solvent (water) that becomes poorer (for the polymer) as the temperature was increased.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Colloidal dispersions have been the subject of many studies, with focus ranging from stability and drug delivery, to self-assembly, patch formation, and so on. The stability of such dispersions can often be controlled by pH and temperature variation, or with additives, such as salt or polymers. One advantage in a system where polymers are used is their ability to mediate attractive, as well as repulsive, interactions between the particles, depending on parameters such as polymer length, solvent quality, or the presence of grafting bonds to the particles. This may facilitate a controlled stability. Crystallization of colloidal particles has also been investigated in many soft matter studies, and the coexistence between “gas” and ”liquid” phases can often be regulated by polymer properties. , Previous work , has established thermoresponsive aggregation, or cluster formation, in aqueous dispersions containing polystyrene (PS) particles, carrying a layer of grafted short polyethylene glycol (PEG) chains. A temperature increase from an ambient value, at which the dispersion remained sterically stabilized, caused a reduced solubility of the polymer grafts, which eventually resulted in gelation, aggregation, or cluster formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation